Financial planning knowledge, financial planning behavior, and adequacy of retirement savings: Evidence from personnel at Prince of Songkla University, Hatyai Campus (Journal of Namibian Studies : History Politics Culture, 2023)
The purpose of this study is to assess the level of financial planning knowledge and behaviors influencing the adequacy of retirement savings among staff in government regulatory agencies. Prince of Songkla University (PSU) was deployed to be the evidence since it is one of the biggest universities in Thailand. Questionnaires were adapted for data collecting by using simple random sampling technique. In this paper, the data was collected from 200 samples. The statistics for data analysis were multiple regression at a significance level of 0.05. The findings indicated that the highest-level areas of knowledge are revenue and expenses management, and retirement planning. The adequacy of savings for retirement of most of the participants had insufficient savings for retirement. The hypothesis testing revealed that insurance planning and retirement planning behavior affected retirement saving adequacy. This research shows that organizations should consider providing retirement savings benefits to their staff. Moreover, organizations involved in providing personal financial planning knowledge should play a role in providing an activity to adjust retirement savings planning behavior for people to reduce financial problems and increase the quality of life for people in retirement.